Contemporary Russian Corruption (Archives of Criminology, 2008)
The author presents a brief history of Russian corruption, which started in the 9th–10th centuries and still exists, seen as a common way to solve various problems, as confirmed in various surveys. The data show that tolerance to corruption is still growing. The author points out some of the factors that might influence the current level of corruption and claims that it is still the main problem in Russia. Further, he presents possible ways of dealing with corruption: creating one institution responsible for dealing with corruption instead of leaving it to multiple people and institutions, increasing the independence of businesses and individuals, increasing the independence and prestige of courts (judges), developing civil society, increasing the salaries of officials, bringing back the freedom of the press and of speech, forming a corresponding social consciousness, and forming the political willpower to decrease the extent of corruption. In the author’s opinion, it is particularly difficult to overcome the corruption in contemporary Russia, as it remains deeply connected with the ones should start the battle – the government.